Using in silico approaches to ascertain selective novel orthosteric and allosteric inhibitors of plasmodium falciparum Prolyl-tRNA synthetase for the development of antimalarial drugs - Ramahala, Rabelani (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Bioinformatics)
Access restricted. Exxpected release in 2026.
Keywords: Uncatalogued